การจัดการความรู้ทุนชุมชนเพื่อการส่งเสริมการจัดการที่ยั่งยืนของตำบลแม่เปา อำเภอพญาเม็งราย จังหวัดเชียงราย : Knowledge Management of Community Capital to Support Sustainable Management of Communities in Mae Pao Sub-district, Phaya Mengrai District, Chiang Rai Province - พระสุนิล, จามรี (Journal of Humanities and Social Sciences (HUSOKKU), 2020)
The objectives of this study were community capital and knowledge management of community capital to support the sustainable management of communities in Mae Pao sub-district, Phaya Mengrai district, Chiang Rai province. To study in key-informants Including community leaders, folk philosopher, representatives from Mae Pao subdistrict administrative organization, educational institutions, religions, and various organizations in the community consisting of 50 people. The results show that Mae Pao sub-district were a semi-urban and multicultural society. The Mae Pao community capital means things that are in the community consisting of physical, cultural, natural resources and human resources. Which causes the learning community to adapt and survive in the development trend and social change. Knowledge management of community capital to strengthen communities is an important strategy for national development. And the community strength is the starting point for development with the concept of social development according to alternative development theory. Knowledge enhancement of tacit knowledge to community information was wisdom, socio-geographic, community capital to learning exchange with other external agencies and within the community which can propel the Mae Pao community to become a sustainable management community and strength.